Study of the functional performance of students in a special medical group after coronavirus infection - Yudenko, I.E.; Shorshina, P.E.; Malkov, M.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to investigate the effect of moderate-intensity walking on heart rate variability in students who have been assigned to a special medical group and have had coronavirus infection. Methods and structure of the study. The study was conducted at the Department of Medical and Biological Foundations of Physical Culture at Surgut State University. The study of heart rate variability was carried out using the Varicard 3.0 software and hardware complex. The sample consisted of 31 people, including 15 young men and 16 young women, with an average age of 19.6±3.7 years. Results and conclusions. The study revealed the positive effect of a six-minute walk of moderate intensity on the functional indicators of the autonomic nervous system (ANS) of students in a special medical group who had recovered from COVID-19.